Analisa Rancang Bangun Mesin Pencacah Rumput Untuk Pakan Ternak - Liandy, Andry Jefry; Pusvyta, Yeny; Budiman, Arie Yudha (Jurnal Multidisiplin Dehasen (MUDE), 2025)
Livestock farmers need to provide sufficient grass to be cut into animal feed every day. Farmers in Pinrang and the surrounding area still use sickles to cut grass. Therefore, when the grass is dense, it requires additional time and labor. The purpose of this grass cutting machine for animal feed was to build a grass chopper and assess its production capacity and effectiveness. Test data was analyzed using a comparative approach, which reflects the productivity level of the equipment. The findings showed that the grass cutting process involves rotating cutting blades. The selected transmission system has a single transmission consisting of a pair of 2.5 mm diameter pulleys for the motor and a 2.5 mm diameter pulley for the drive component. Chopping 0.5 kg of elephant grass using three cutting blades at rotational speeds of 730 rpm, 1100 rpm, and 1850 rpm took 8 seconds, 9.2 seconds, and 10.6 seconds, respectively. The analysis showed that the optimal method for chopping grass is to use three cutting blades. From this data, it can be concluded that as the chopper's rotational speed increases, the resulting chopped capacity also increases.